Efficient solvent-free cationization of alkylpolyglycoside based surfactant compositions using natural glycine betaine. Issue 6 (13th November 2015) - Pérusse, D.; Guégan, J. P.; Rolland, H.; Guilbot, J.; Benvegnu, T.
Abstract : Solvent-free transformation of alkylpolyglycosides into 100% bio-based cationic sugar surfactants proceeded efficiently using a natural glycine betaine-derived cationizing agent. Abstract : We describe here a new strategy for the preparation of 100% bio-based sugar based cationic surfactants using glycine betaine butyl ester as the cationizing agent. We first studied NaHCO3 -catalyzed transesterification reactions of pure fatty alcohols and equimolar mixtures of alkyl glucosides or xylosides and fatty alcohols. Using solvent-free processes, moderate to high levels of cationization (48–90%) concerning both fatty alcohols and carbohydrates, were obtained with a certain regioselectivity toward C6 and/or C3 positions in thed -glucose andd -xylose series. This synthetic approach can also be extended to commercial alkylpolyglycosides containing large proportions of fatty alcohols (90–96%) to provide original cationized glycoside compositions, as (co-)emulsifiers.